Identification and physiological characterization of low potassium tolerant germplasm in Tibetan Plateau annual wild barley - Zhu Bo; Zeng Jianbin; Wu Dezhi; Cai Shengguan; Yang Li’na; Zhang Guoping (浙江大学学报. 农业与生命科学版)
First, a hydroponic experiment was conducted to compare the difference in low potassium (K) tolerance among 99 Tibetan annual wild barley genotypes. The wild barleys that were examined showed a significant difference in low K tolerance, with XZ107, XZ153 and XZ159 being high tolerant, and XZ141 being high sensitive. Second, these four wild barley genotypes as well as two cultivated barley cultivars were used to investigate the genotypic difference in K use efficiency (KUE), net photosynthesis and expression of HvHAK1. The results showed that the values of these parameters were larger in low K tolerant genotypes than in sensitive ones. In addition, the association analysis using DArT markers indicated that tissue K concentration was controlled by multiple genes. The current results also showed that Tibetan annual wild barley may provide elite germplasm or genes for genetic improvement of KUE in barley and other crops, and relative tissue biomass as well as KUE under low K relative to normal K level can be used as the reliable index for evaluating low K tolerance in barley.